Cognitive and language deficits in vascular dementia - Vasilijević, Slavica R.; Vuković, Mile; Jerkić, Lana (Acta medicae Medianae, 2021)
Vascular dementia (VaD) represents a progressive decline in cognitive functions to the extent that it interferes with the performance of daily activities. It is a relatively common form of dementia that occurs in frequency immediately after Alzheimer’s disease. VaD is associated with cerebrovascular disorders mainly in the left hemisphere of the brain. It is clinically manifested by disorders of language, memory, reasoning, and executive functions. However, visuospatial deficits, deficits of attention, praxia, reasoning, and other disorders can also be manifested. The nature of the symptoms of cognitive impairment in VaD is still not sufficiently known. It is believed that the appearance of language disorders in the form of aphasia also contributes, and complicates the assessment of memory and other cognitive functions. Important parts of the diagnosis of VaD are neurological and neuropsychological assessment, while treatment is based on drug therapy, psychosocial support, and speech-language therapy.